Asymmetric electrode geometry induced photovoltaic behavior for self-powered organic artificial synapses. (31st December 2021) - Zou, Shizan; Wang, Hengyuan; Guo, Jianhang; Jiang, Sai; Hao, Ziqian; Pei, Mengjiao; Xu, Xin; Li, Yating; Chen, Jiaming; Wang, Junzhuan; Li, Yun
Abstract: Opto-electronic synapses have attracted considerable attention because of their promising potential in artificial visual perception systems for neuromorphic computing. Despite remarkable progress in mimicking synaptic functions, reduction of energy consumption of artificial synapses is still a substantial obstacle that is required to be overcome to promote advanced emerging applications. Herein, we propose a zero-power artificial optoelectrical synapses using ultrathin organic crystalline semiconductors, which can be self-driven by exploiting the photovoltaic effect induced by asymmetric electrode geometry contacts. The photogenerated charge carrier collection at the two electrodes is unbalanced due to the asymmetric contacts, leading to the in-plane current without bias voltage. Our devices successfully mimic a range of important synaptic functions, such as paired-pulse facilitation and spike rate-dependent plasticity. Furthermore, we demonstrate that our devices can realize the simulation of image sharpening under self-driven optical-sensing synaptic operations, offering prospects for the development of retinomorphic visual systems.